Spectral characteristics and ultrahigh sensitivities near the dispersion turning point of optical microfiber couplers - Li, Kaiwei (2020)
We present a systematic study on the spectral characteristics and ultrahigh sensitivity near the dispersion turning point (DTP) of optical microfiber couplers. Numerical simulations reveal that a DTP exists when the group effective refractive index (RI) difference between the even mode and the odd mode equals zero, where both ultrahigh positive RI sensitivities and negative RI sensitivities can be achieved. The position of the DTP is dependent on the coupler width, and it always exists over the surrounding RI (SRI) range of 1.333-1.41, which enables the ultrasensitive RI sensing in this wide RI range. Then, we studied the interference spectra characteristics around the DTP both theoretically and experimentally. We further experimentally demonstrate ultrahigh sensitivities of 59624 nm/refractive index unit (RIU) and -58470 nm/RIU around the SRI of 1.333 and 26999 nm/RIU and -29267 nm/RIU around the SRI of 1.35, respectively. High figure of merits of 4192 and 5280 are also achieved around the SRI of 1.333 and 1.35, respectively. Finally, utilizing the exceptional RI sensitivity, we demonstrate an ultrasensitive temperature sensor with a negative sensitivity of -15.23 nm/°C and a positive sensitivity of +16.78 nm/°C.